(untitled) (Mongolian Journal of Humanities and Social Sciences, 2025)
This article explores the traditional Mongolian burial rites for the deceased and the custom of levirate marriage (widow inheritance), as well as the conflict between Begter and Temuujin in The Secret History of the Mongols. It explains that Temuujin, during his youth, killed his half-brother Begter with the help of his full brother Khasar. This act was closely tied to the levirate tradition, as Begter, upon reaching adulthood, could have claimed their mother, Uelun, as his wife—thereby gaining leadership over the Khiad Borjigin clan. Thus, Temuujin’s elimination of his half-brother was both a political move and a response to the implications of the levirate custom. The article discusses how this event reflects the intersection of traditional marital practices and power struggles in early Mongol society. Улирч гэрлэх ёс ба “Монголын нууц товчоон” дахь Бэгтэр, Тэмүжин нарын зөрчил Хураангуй: Энэхүү өгүүлэлд монголчуудын үхэгсдээ оршуулах хойлгын ёс ба улирч гэрлэх (левират) ёсны уламжлал хийгээд “Монголын нууц товчоон”-ны Бэгтэр, Тэмүжин нарын зөрчлийг тайлбарласан байна. Ингэхдээ Тэмүжин бага насандаа өөрийн эцэг нэгтэй ах Бэгтэрийн дүү Хасарын хамтаар хөнөөсөн нь улирч гэрлэх ёстой холбоотой, учир нь Бэгтэр өсөж том болоод Өэлүн эхийг хатнаа болгон авах улмаар хиад боржигоны эзэн болох магадлалтай байсан тул ийнхүү ахыгаа өөрийн замаас зайлуулсан нь нэг талдаа улирч гэрлэх ёс, нөгөө талдаа улс төрийн шийдэл хийсэн тухай өгүүлсэн байна. Түлхүүр үг: Хойлгын ёс, олдвор, улирч гэрлэх ёс, левират гэрлэлт